Sex Differences of the Diabetic Heart - Fourny, Natacha; Beauloye, Christophe; Bernard, Monique; Horman, Sandrine; Desrois, Martine; Bertrand, Luc (Frontiers in Physiology, 2021)
Type 2 diabetes is a chronic disease associated to micro- and macro-vascular complications, including myocardial ischemia, but also to a specific and intrinsic cardiac dysfunction called diabetic cardiomyopathy (DCM). Both clinical and animal studies have demonstrated significant sex differences in prevalence, pathophysiology, and outcomes of numerous cardiovascular diseases (CVDs), including those associated to metabolic syndrome and diabetes. Accumulating evidence from pioneer studies such as the Framingham study, showed that risk of CVDs is higher in diabetic women compared to diabetic men. Women have 50% higher risk of coronary artery diseases than men, and increased mortality when exposed to acute myocardial infarction. Clinical studies also revealed a sexual dimorphism in the incidence and outcomes of DCM. Based on these clinical findings, growing experimental research was initiated to understand the impact of sex on CVDs associated with diabetes, with the goal to identify the molecular mechanisms involved. In this review, we summarize the salient findings about sex differences in cardiovascular complications of diabetes, with a particular focus on ischemic diseases and DCM. Contribution of sex hormones, oxidative stress, metabolism, endothelial dysfunction is particularly highlighted. Current medicine tending towards a more personalized care of patients, we finally discuss the importance of sex becoming as determinant in the treatment of diabetes-associated cardiac diseases to encourage inclusion of both male and female in clinical and preclinical studies.